2019
DOI: 10.1016/j.cmet.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Proglucagon-Derived Peptides Are Essential for Regulating Glucose Homeostasis in Mice

Abstract: Highlights d The mouse and human pancreas contain low levels of active GLP-1 d The gut enteroendocrine system is responsible for 95% of circulating active GLP-1 d The proximal gut sustains normal plasma GLP-1 levels in response to enteral glucose d Gut Gcg expression controls glucose tolerance and gastric emptying

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 50 publications
(83 reference statements)
2
81
1
Order By: Relevance
“…2A,B), consistent with the higher number of GLP-1-positive cells observed in Fig. 1 as well as with a recent work comparing mouse vs. human pancreatic GLP-1 16 . We then tested whether paracrine GLP-1 signaling is necessary for normal glucose-stimulated insulin secretion by performing static GSIS studies in the presence of exendin-(9-39) (Ex9), a specific GLP-1 receptor (GLP-1R) antagonist 17 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2A,B), consistent with the higher number of GLP-1-positive cells observed in Fig. 1 as well as with a recent work comparing mouse vs. human pancreatic GLP-1 16 . We then tested whether paracrine GLP-1 signaling is necessary for normal glucose-stimulated insulin secretion by performing static GSIS studies in the presence of exendin-(9-39) (Ex9), a specific GLP-1 receptor (GLP-1R) antagonist 17 .…”
Section: Resultssupporting
confidence: 92%
“…All animals used in this study were housed in facilities with a standard light-dark cycle and fed ad libitum. Pancreatic mouse islets were isolated from male [12][13][14][15][16] week old C57BL/6J and B6.Cg-Lep ob /J (ob/ob) (Jackson Laboratory, ME) as described previously 52 . Briefly, islets were isolated by collagenase digestion and Histopaque gradient (Sigma, #10771).…”
Section: Methodsmentioning
confidence: 99%
“…The reason for this discrepancy may be that different parts of intestine were investigated (the lower ileum in our study, while the proximal duodenum in Gu et al ’s study16). A recent study showed that deletion of Gcg gene in the mouse distal gut reduced the plasma active GLP-1 levels, highlighting the essential role of the distal gut in the regulation of GLP-1 secretion 30. Considering the distribution of L-cells, the lower ileum was more suitable for evaluating L-cell mass and GLP-1 content than the proximal duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, further studies investigating L-cells in the entire intestinal tract are needed to provide detailed changes of the L-cell mass. Although gut-derived GLP-1 is essential for glucose homeostasis,30 it is worth noting that we could not exclude other sources of GLP-1. For example, our previous study showed that pancreatic α-cells could express PC1/3 and process Gcg into GLP-1 after GCGR mAb treatment,6 suggesting that the increased plasma GLP-1 level might also derive from pancreatic α-cells.…”
Section: Discussionmentioning
confidence: 99%
“…We purchased male and female C57BL/6 mice for use in experiments and breeding from the Jackson Laboratory. Lepr cre , Ppg cre , and Ppg fl mice have been described (16,20,34,35) and were propagated by intercrossing homozygous mice of the same genotype. Cck cre mice were purchased from the Jackson Laboratory (stock no.…”
Section: Methodsmentioning
confidence: 99%